Analisis Komparatif Performa Latensi dan Stabilitas Koneksi Wemos D1 Mini Vs Esp32-C3 Minipada Sistem Kendali Jarak Jauh Berbasis IoT - Supriyade; Annisa Risqi Sulistya Kusuma Wardhani; Fery Updi (Pusat Riset dan Inovasi Nasional, 2026)
Abstract: This research conduct a comparative analyisis of connectivity performance between the Esp8266 (Wemos D1 Mini) and the Esp32-C3 Miniwithin internet of things (IoT) remote control systems. The primary problem addressed is the critical need for low latency and high connection stability in real-time difital infrastructure management, where developers often face a trade-off between costt-eficiency and hardware performance. The objective of this study is to empirically evaluate which microcontroller provides supervisor responsiveness. An experimental methode was proposed by measuring two key parameters : Receive Signal Strength Indicator (RSSI) and data transmission latency accros various distances and physical obstacles. The mind findings reveal that the Esp32-C3 Mini, utilizing the RISC-V architecture, demontsrates more consistent signal stability and significantly lower overage latency compared to the Esp8266, particularly in indoor environments with structural interference. In conclusion, the Esp32-C3 Mini is more effective successor to the Esp8266 for moder IoT applications that require high realibility and rapid respons times. Keywords: IoT; Esp8266 Wemos D1 Mini; Esp32-C3; Latency; RSSI; Remote Control;